Hard road west : history & geology along the Gold Rush trail - Meldahl, Keith Heyer (University of Chicago Press, 2007)
In 1849 news of the discovery of gold in California triggered an enormous wave of emigration toward the Pacific. Lured by the promise of riches, thousands of settlers left behind the forests, rain, and fertile soil of the eastern United States in favor of the rough-hewn lands of the American West. The dramatic terrain they struggled to cross is so familiar to us now that it is hard to imagine how frightening--even godforsaken--its sheer rock faces and barren deserts seemed to our forebears. This book brings their perspective vividly to life, weaving together the epic overland journey of the covered wagon trains and the compelling story of the landscape they encountered. Geologist Meldahl uses diaries and letters of the settlers themselves--as well as the countless hours he has spent following the trail--to reveal how the geology and geography of the West directly affected our nation's westward expansion.--From publisher description.